Black legacies : race and the European Middle Ages - Ramey, Lynn Tarte, 1964- (University Press of Florida, 2014)
Black Legacies looks at color-based prejudice in medieval and modern texts in order to reveal key similarities. Bringing far-removed time periods into startling conversation, this book argues that certain attitudes and practices present in Europe's Middle Ages were foundational in the development of the western concept of race. Using historical, literary, and artistic sources, Lynn Ramey shows that twelfth- and thirteenth-century discourse was preoccupied with skin color and the coding of black as "evil" and white as "good." Ramey demonstrates that fears of miscegenation show up in all medie